The SOUX AGN sample: SDSS–XMM-Newton optical, ultraviolet, and X-ray selected active galactic nuclei spanning a wide range of parameter space – sample definition. Issue 2 (20th January 2023) - Kynoch, Daniel; Mitchell, Jake A J; Ward, Martin J; Done, Chris; Lusso, Elisabeta; Landt, Hermine
Abstract: We assemble a sample of 696 type 1 active galactic nuclei (AGN) up to a redshift of z  = 2.5, all of which have an SDSS spectrum containing at least one broad emission line (H α, H β, or Mg ii ) and an XMM-Newton X-ray spectrum containing at least 250 counts in addition to simultaneous optical/ultraviolet photometry from the XMM Optical Monitor. Our sample includes quasars and narrow-line Seyfert 1s: thus our AGN span a wide range in luminosity, black hole mass, and accretion rate. We determine single-epoch black hole mass relations for the three emission lines and find that they provide broadly consistent mass estimates whether the continuum or emission line luminosity is used as the proxy for the broad emission line region radius. We explore variations of the UV/X-ray energy index αox with the UV continuum luminosity and with black hole mass and accretion rate, and make comparisons to the physical quasar spectral energy distribution model qsosed . The majority of the AGN in our sample lie in a region of parameter space with 0.02 < L / L Edd < 2 as defined by this model, with narrow-line type 1 AGN offset to lower masses and higher accretion rates than typical broad-line quasars. We find differences in the dependence of αox on UV luminosity between both narrow/broad-line and radio-loud/quiet subsets of AGN: αox has a slightly weaker dependence on UV luminosity for broad-line AGN and radio-loud AGN have systematically harder αox .